Exploration of Sāṁkhya Basing on Prakṛti and Puruṣa in the Śrīmad Bhāgavata - Pokhrel, Mohan Kumar (Dristikon: A Multidisciplinary Journal, 2020)
The Sāṁkhya philosophy relating to Prakṛti and Puruṣa discusses the ultimate reality of the universe in the Śrīmad Bhāgavata Mahāpurāṇa. When the balanced state of Prakṛti is disturbed by Puruṣa, the process of evolution takes place in the universe. This article concentrates on the significance of Prakṛti and Puruṣa as the base of the Sāṁkhya philosophy. At the same time, it also deals with the impression of these two components of nature in this philosophy for the creation and maintenance of this universe. To analyze the Sāṁkhya philosophy relating to Prakṛti and Puruṣa, this study has been used as overall theoretical approach. It is important in order to present how the Bhāgavata reflects the use of Prakṛti and Puruṣa for the creation of theuniverse. The interpretive method is used for the exploration of Prakṛti and Puruṣa in the text.The findings of the investigation suggest that Prakṛti and Puruṣa are the bases of the Sāṁkhya philosophy and the readers should have knowledge about this philosophy of the very ancient time. The prime conclusion drawn from this research is that Prakṛti and Puruṣa are the main elements of Nature from which the creation and the existence of the universe are possible.